Language Styles Used in English Commercial Product and Educational Advertisements on Internet - Saputri, Yuli Elyanur; Barus, Jumat; Muna, Hayatul (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
This research aims to analyze the kinds of language styles used in English Commercial Products and Educational Advertisements on the internet. This research used a qualitative descriptive technique by collecting fifteen English Commercial Products and five Educational Advertisements from the internet and using them as documentation. Data analysis techniques used are data condensation, data display, and drawing conclusion/verification. As the results of this research, the researcher found six language styles used in commercial product advertisements: spokesperson, problem solution, demonstration, a slice of life, comparison, and combination of problem solution and comparison style; and three language styles used in the educational advertisement: hard sell, soft sell, and straightforward style.